Sexual agency of young widows in Malay culture: An ethnographic study in Serdang Village, South Bangka - Citra Asmara Indra; Emy Susanti; Musta'in Mashud (Masyarakat, Kebudayaan dan Politik, 2021)
Patriarchal culture is part of Malay society. However widows in Serdang Village, South Bangka gain agency in the midst of patriarchal culture. They find strategies in meeting their sexual needs after getting their agency. This study looks at how women find their agency and strategies to fulfill their sexual needs in the midst of the Serdang Village community which is still heavily associated with its Malay culture. The ethnographic research method was carried out to explore the agency of young widows in the village using Agency Theory from Lois McNay and Gayle Rubin’s thought “The Charmed Cyrcle” as an analytical knife to dissect the problems that exist in Serdang Village. This study found that young widows use strategies to fulfill their sexual needs, either by connecting with a boyfriend without getting married, watching adult videos, connecting with customers on a consensual or paid basis. This study concludes that the agency that has been built by the widows allows them to express their sexual needs freely.